Transit-oriented development (TOD) as a facilitator for urban development integration: case study: Du Toit train station precinct, Stellenbosch - Mafame, Thendo (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.